The development of equating application for computer based in physics HOTS category - Yetti Supriyati; Deni Iriyadi; Ilham Falani (OmniaScience, 2021)
This study aims to develop a score equating application for computer-based school exams using parallel test kits that have 25% anchor items, the items are arranged according to the HOTS (High Order Thinking Skill) category and use a scientific approach according to the characteristics of physics lessons. So that the questions are made using stimulus, options, logical and systematic. The research method used is Research and Development (R&D), which begins with an analysis of the current needs of schools and takes advantage of technological developments so that it makes it easier for schools to organize, and then continued in the literature study to design a school exam model with its devices. Items as instruments for school exams were analyzed using the RASCH model. The principle of equating used in application development is the linear equating method.